Chatgpt Acceptance and Use For Generation Z Pre-Service Science Teacher: A Survey Study - Adam, Wahyuni; Pratama, I Putu Yogi; Handika, Ilham; Qudratuddarsi, Hilman (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Over recent decades, AI in education has evolved into adaptive, personalized tools like ChatGPT. For Generation Z pre-service science teachers, ChatGPT supports lesson planning, reflection, and simulation. Using TPB and UTAUT2, this study explores factors influencing ChatGPT acceptance and use, offering insights to inform future teacher education programs. This study used a quantitative, cross-sectional survey design with 221 pre-service science teachers. Data were collected online using a validated instrument based on UTAUT and TPB constructs. Statistical analysis involved descriptive statistics, Pearson correlation, t-tests, and ANOVA to examine ChatGPT acceptance and use patterns. The study found that Generation Z pre-service science teachers generally hold neutral to slightly positive attitudes toward ChatGPT, recognizing its ease of use and potential benefits. However, social influence, habit formation, and actual usage remain weak. Descriptive and correlation analyses show that habit, facilitating conditions, and hedonic motivation are the strongest predictors of behavioral intention and use. These results suggest that institutional support and strategies to increase habitual and enjoyable use are key to enhancing ChatGPT adoption in educational settings.